Kompetensi, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai RSUD Tarakan Provinsi Kalimantan Utara - Purwaningsih; Nurul Hidayat; Milwan (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
The purpose of the study was to analyze the influence of competence, work discipline and work environment on employee performance at Tarakan Hospital, North Kalimantan Province. The type of research that will be used in this research is to use quantitative research, namely the survey method. The theories used as references in this research are competency theory (Maulana, A, 2020), work discipline (Rivai, V, 2014), work environment (Sedarmayanti, 2017) and performance theory (Gomes, 2010). To get a representative sample, according to Hair et al (2006), the question items are multiplied by 5, so the number of respondents used is 135 respondents. The method used is descriptive statistics, coefficient of determination, multiple linear regression coefficients and hypothesis testing. Research Results 1) Competence has a significant influence on performance, meaning that competence contributes to performance, the better competence, the better performance; 2) Work discipline has a positive and insignificant effect on performance, meaning that work discipline contributes to performance, 3) the work environment has a significant influence on performance, then the work environment contributes to performance, the better the work environment, and will improve performance.